Exploring Extubation Readiness in Guillain-Barré Syndrome: A Case Report and Literature Review - Victoria Watson MD; Saif Ghishan MD; Tata Avalishvili MD; Sinen Zeleke MD; Saron Tigabe MD; Anderson White BS; Fuad Zeid MD, MSc, FACP; Zakaria Alagha MD, MSc (Journal of Investigative Medicine High Impact Case Reports)
Guillain-Barré Syndrome (GBS) is an acute immune-mediated polyneuropathy causing rapidly progressive muscle weakness and often respiratory failure, requiring mechanical ventilation in 30% of cases. Successful weaning and extubation are crucial, focusing on readiness for spontaneous breathing trials, optimal timing, and minimizing complications such as ventilator-associated pneumonia and extubation failure. This case report describes an 83-year-old male with multiple comorbidities who was intubated after his negative inspiratory force dropped below −30 cm H₂O and treated with plasmapheresis, leading to partial improvement. Despite not meeting standard extubation criteria, he was successfully extubated, maintained stable respiratory function, and was safely discharged. This case highlights the challenges of extubation in GBS patients, where advanced age, decreased physiological reserve, and comorbidities increase the risks of prolonged intubation and complications. This case also highlights the need for individualized extubation strategies in GBS, particularly in elderly patients who may not meet standard criteria. Tailored approaches can still lead to successful outcomes. Based on our institutional experience, we propose factors that predict the success or failure of extubation in these patients. Further research is needed to refine predictive markers and improve extubation success in this population, ultimately enhancing outcomes and reducing ICU and hospital stays.